TAFSIR BERBASIS LINGUISTIK “AL-TAFSĪR AL-BAYĀNI LI AL-QUR’ĀN AL-KARĪM “ KARYA ‘ĀISYAH ‘ABDURRAHMĀN BINTU SYĀT - Fuad Thohari (Sunan Kalijaga State Islamic University Yogyakarta, 2009)
Two outstanding features, which Al-Tafsir al-Bayani li al-Qur’an al-Karim has, are, firstly, it’s written by a woman, named Binti Syati’- and secondly, its method ofinterpretation uses linguistic approach. This book of linguistic interpretation is an application of the method of modern interpretation invented by Amin al-Khuli. This study aims to explain that Al-Tafsir al-Bayani has its theoretical framework on linguistic approach. Firstly, it interprets Qoran thematically based on its surah unity, in this case it takes 14 short surah. Secondly, it focuses on the words’ generality, instead of the prophetic events. Thirdly, it analyzes the meaning (dilalah)of Qoran in Arabic. Forth is that it holds on to its contex of nash.